Learning Motivation and Mothers’ Democratic Parenting Style on Learning Behaviours - Mayangsari, Rr. Hayu; Kristianingsih, Sri Aryanti; Adiyanti, Maria Goretti (Bulletin of Counseling and Psychotherapy, 2024)
This study investigated into the connection between learning motivation and mothers’ democratic parenting styles, exploring their impact on adolescent learning behaviors through a correlational quantitative approach. The research involved a sample of 216 high school students from Manado Independent School, carefully selected using simple random sampling. Data was gathered through the distribution of questionnaires, including the Learning Motivation Questionnaire, the Parenting Style and Dimension Questionnaire (PSDQ) for Adolescents, and the Learning Behaviors Scale, which provided valuable insights into the dynamics at play. The data obtained were analyzed using multiple linear regression techniques. The results of the partial regression analysis revealed a significant positive correlation between learning motivation and learning behaviors, with a regression coefficient of 0.400 and a significance value of 0.000 (p<0.05). In contrast, the democratic parenting style showed no significant contribution to learning behaviors, as evidenced by a regression coefficient of -0.07 and a significance value of 0.770 (p>0.05). Overall, the findings of the study revealed a significant simultaneous contribution of both learning motivation and mothers’ democratic parenting styles to adolescent learning behaviors. With a coefficient of determination of 0.653 and a significance value of 0.000 (p<0.05), the results highlighted that these factors played a crucial role in enhancing learning behaviors. This, in turn, holds the potential to improve academic performance and overall learning outcomes among adolescents.